Supercontinuum generation with microstructured fibers made of soft glass - Buczyński, Ryszard; Pysz, Dariusz; Kujawa, Ireneusz; Korzeniowski, Jakub; Martynkien, Tadeusz; Berghmans, Francis; Thienpont, Hugo; Stępień, Ryszard (Photonics Letters of Poland, 2009)
In this paper we report on the fabrication of a micro-structured fiber made of in-house synthesized silicate glass, with a nonlinear Kerr refractive index of 4.0 10-15 cm2/W. The fiber uses three rings of holes around a slightly elliptical core with dimensions 2.6 um x 3.4 um. It has a birefringence of about 10-3 at 1.5 um and zero dispersion wavelengths at 860 nm and 870 nm. Using this fiber we have demonstrated ultra broadband supercontinuum generation in the 400-1600 nm range for a 19.5 cm sample pumped with 100 fs pulses with central wavelength of 755 nm and energy of 2 nJ. The broadband generation of 200 nJ in the 650-850 nm range with pulse energy at the level of 0.57 nJ is also observed with the same structure. Full Text: PDF References: R. Alfano, The Supercontinuum Laser Source: Fundamentals with Updated References, (Springer, 2005). J. M. Dudley et al.,"Supercontinuum generation in photonic crystal fiber", Rev. Mod. Phys. 78. 1135-1184, (2006)[CrossRef] A.Ferrando et al.,"Full-vector analysis of a realistic photonic crystal fiber", Opt. Lett. 24, 276 (1999)[CrossRef] I.Kujawa et al., "Development of all-solid photonic crystal fibers", Proc. SPIE Vol. 6182, 61822Q (2006)[CrossRef]